Factors that influence youth participation in oil palm plantation among second generation settlers at Felcra Berhad (Lekir, Perak) / Nor Fazilah Abdullah - Abdullah, Nor Fazilah (Faculty of Plantation and Agrotechnology, 2018)
Oil palm is a major plantation crop for the economy of Malaysia. However, nowadays youth are more attracted to the trendy jobs including in business rather than to work at agriculture sector. It shows that youth are very demanding to work with higher income. This research tries to determine the variables namely interest, perception, salary and environment towards youth participation to work in plantation among 136 respondents in FELCRA Berhad Kawasan Lekir, Perak that have been selected randomly. The targeted respondents who are the second generation is ranging between 17-39 years old. Correlation analysis and multiple linear regression analysis were conducted to analyse data. The results showed that the environment is not significant toward youth participation in oil palm plantation but the other factors which are interest, perception and salary have significant relationship toward youth participation in oil palm plantation. In addition, the result also showed that the interest factor is most dominant factor but has low relationship toward the youth participation to work in oil palm plantation sector. The result also showed that the mean 15.3% of the interest and salary affect the youth to participate in oil palm plantation sector while the another 84.7% is caused by other factors. The lack of experience among the youth to working in oil palm plantation is one of factor that youth are less interest to participate in this sectors. In order to encourage the interest of the youth participation in this sector, government should support and play roles by providing varieties of program for enrich their skill.